Construction of a vascularized hydrogel for cardiac tissue formation in a porcine model. (10th January 2018) - Myu Mai Ja, K.P.; Lim, Kee Pah; Chen, Allen; Ting, Sherwin; Li, Shi Qi; Tee, Nicole; Ramachandra, Chrishan; Mehta, Ashish; Wong, Philip; Oh, Steve; Shim, Winston
Abstract: Replacing cardiac tissues lost to myocardial infarction remains a therapeutic goal for regenerative therapy in recovering cardiac function. We assessed the feasibility of constructing a macrosized human cardiac tissue construct using pluripotent stem cell‐derived cardiomyocytes or control fibroblasts infused fibrin/collagen hydrogel and performed ectopic implantation in peripheral vascular system of a porcine model for 3 weeks. Finally, an optimized vascularized cardiac construct was explanted and grafted onto porcine myocardium for 2 weeks. Myocardial‐grafted human cardiac constructs showed a nascent tissue‐like organization with aligned cardiomyocytes within the remodelled collagen matrix. Nevertheless, no significant changes in intraconstruct density of cardiomyocytes were observed in the myocardial‐grafted constructs (human embryonic stem cell [hESC]‐derived cardiomyocyte [ n  = 4]: 70.5 ± 22.8 troponin I + cardiomyocytes/high power field [HPF]) as compared to peripherally implanted constructs (hESC‐derived cardiomyocyte [ n  = 4]: 59.0 ± 19.6 troponin I + cardiomyocytes/HPF; human induced pluripotent stem cell‐derived cardiomyocyte [ n  = 3]: 50.9 ± 8.5 troponin I + cardiomyocytes/HPF, p  = ns). However, the myocardial‐grafted constructs showed an increased in neovascularization (194.4 ± 24.7 microvessels/mm 2 tissue, p  < .05), microvascular maturation (82.8 ± 24.7 mature microvessels/mm 2, p  < .05), and tissue‐like formation whereas the peripherally implanted constructs of hESC‐derived cardiomyocyte (168.3 ± 98.2 microvessels/mm 2 tissue and 68.1 ± 33.4 mature microvessels/mm 2 ) and human induced pluripotent stem cell‐derived cardiomyocyte (86.8 ± 57.4 microvessels/mm 2 tissue and 22.0 ± 32.7 mature microvessels/mm 2 ) were not significantly different in vascularized response when compared to the control human fibroblasts ( n  = 3) constructs (65.6 ± 34.1 microvessels/mm 2 tissue and 30.7 ± 20.7 mature microvessels/mm 2 ). We presented results on technical feasibility and challenges of grafting vascularized centimetre‐sized human cardiac construct that may spur novel approaches in cardiac tissue replacement strategy.